Analysing the efficiency of the post provisioning model as a policy tool in public administration : a case study of Mafarana Circuit, Mopani West District, Limpopo Province, South Africa - Motshoane, Relebogile Sarah (My University, 2025)
The purpose of this study was to investigate the efficiency of the post provisioning model as a policy tool in public administration. How it affects the general management of schools, curriculum implementation and learner attainment. A case study was conducted with the focus on Mafarana Circuit, Mopani West District of Limpopo in South Africa. The post provisioning policy determines the number of teachers and resources to be allocated to a school. The qualitative, descriptive research approach was conducted. Data collection was done using semi-structured interviews on Principals, Departmental heads and educators from four schools, 2 secondaries and 2 primary schools of high enrolled and low enrolment. The study revealed that the small schools are negatively affected by the Policy due to the low number of teachers allocated to the schools. This affects teachers’ performance and morale. Principals find themselves overwhelmed with managerial and classroom duties. Many departmental heads are co-opted as schools do not qualify for such posts due to the post provisioning model. The study recommends that the policy be revised in order to serve the curriculum needs of different institutions so that there is equity in terms of access to quality education for all learners
Thesis (MPAM.) -- University of Limpopo, 2025
Keywords: Public administration; Policy; School management; Curriculum implementation; Learner attainment; Public administration -- South Africa; School management and organization -- South Africa